2012
DOI: 10.1063/1.4738779
|View full text |Cite
|
Sign up to set email alerts
|

Filamentary streamer discharges in argon at atmospheric pressure excited by surface plasmon polaritons

Abstract: This paper describes a microwave plasma jet in an argon atmosphere capable of generating filamentary streamer discharges within the entire quartz tube excited by surface waves of surface plasmon polaritons (SPPs) located in the tube. Several discharge streamers are immediately produced at the end of the copper wire when incident power reaches 20 W. From simulations, the wavelength of the surface wave was found to be approximately 5.7 cm. Although the developing streamers induce E-field enhancements favoring di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 24 publications
1
37
0
3
Order By: Relevance
“…Thence, the bulk plasma density n bulk can be calculated 8:3 Â 10 20 m -3 approximately. It should be mentioned that although this density value is consistent with previous studies reported from the similar lowerpower argon microwave plasma jets driven by continues microwave power in ambient air, [3][4][5][6][7][8][9][10][11][12][13][14][15][16]32 the actual plasma density of the pulsed plasma jet is lower than this value, due to the average power absorbed by the electrons lower largely in pulsed discharge with the same peak power amplitude.…”
Section: Experimental Summarysupporting
confidence: 81%
See 4 more Smart Citations
“…Thence, the bulk plasma density n bulk can be calculated 8:3 Â 10 20 m -3 approximately. It should be mentioned that although this density value is consistent with previous studies reported from the similar lowerpower argon microwave plasma jets driven by continues microwave power in ambient air, [3][4][5][6][7][8][9][10][11][12][13][14][15][16]32 the actual plasma density of the pulsed plasma jet is lower than this value, due to the average power absorbed by the electrons lower largely in pulsed discharge with the same peak power amplitude.…”
Section: Experimental Summarysupporting
confidence: 81%
“…According to Eqs. (5) and (18) electron density and also square proportional to the electric field. Thence, although the electron density peaks at 25 ls, the absorbed power density gets its maximum value at 12 ls, due to the peak electric field occurring at 10 ls.…”
Section: Simulation Results and Discussionmentioning
confidence: 98%
See 3 more Smart Citations